2017
DOI: 10.1016/j.jenvman.2017.04.072
|View full text |Cite
|
Sign up to set email alerts
|

Changes imposed by pyrolysis, thermal gasification and incineration on composition and phosphorus fertilizer quality of municipal sewage sludge

Abstract: Fertilizer quality of ash and char from incineration, gasification and pyrolysis of a single municipal sewage sludge sample were investigated by comparing composition and phosphorus (P) plant availability. A process for post oxidation of gasification ash and pyrolysis char was developed and the oxidized materials were investigated as well. Sequential extraction with full elemental balances of the extracted pools as well as scanning electron microscopy with energy dispersive X-ray spectroscopy were used to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 67 publications
7
53
0
1
Order By: Relevance
“…Municipal sewage sludge is currently a major problem in China's urbanization process, and its improper disposal may result in high levels of environmental pollution [28,29]. Agricultural application, composting, and incineration cannot be widely adopted due to economic or technical reasons, which renders the existing problem of municipal sewage sludge di cult to solve [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Municipal sewage sludge is currently a major problem in China's urbanization process, and its improper disposal may result in high levels of environmental pollution [28,29]. Agricultural application, composting, and incineration cannot be widely adopted due to economic or technical reasons, which renders the existing problem of municipal sewage sludge di cult to solve [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Many other problematic issues may be overcome by fuel design, for example through proper mixing. Recent studies on these issues have indicated many potential benefits related to moisture content, ash melting-related issues and ash/char by-product quality (Skoglund et al, 2016;Thomsen et al, 2016;Thomsen et al, 2017b;Thomsen et al, 2017c).…”
Section: Biomass Resourcesmentioning
confidence: 99%
“…Low-temperature circulating fluidized-bed schematic design and ash/char products. Adapted with permission fromThomsen et al (2017c).…”
mentioning
confidence: 99%
“…Thermal conversion of sewage sludge by incineration, gasification or pyrolysis can be used to combine removal of organic contaminants with additional benefits such as high energy output [9,10]. Depending on the thermal conversion method used, a residual ash or biochar product that is free of pathogen contamination, reduced in weight and volume and high in P concentration compared with the raw sludge is obtained [10]. However, the P contained in these products is often poorly available to plants, resulting in rather low uptake efficiency when recycled back to agriculture [11][12][13][14].…”
Section: A C C E P T E Dmentioning
confidence: 99%